Análisis de la viabilidad técnico-financiera de un sistema de energía fotovoltaica en una finca en Villa de Leyva, Boyacá, Colombia (2021)
This work develops the design of a photovoltaic solar energy system to energetically supply a residential farm located in the municipality of Villa de Leyva, Boyacá. For this, a description of the most relevant aspects is presented that allow a diagnosis of the site where the project is planned to be carried out. Initially, a description of the farm is made using a top view map, a topographic survey map, a farm location map, and a map of available areas to implement the photovoltaic energy system. Additionally, an analysis of the political, economic, sociocultural, and technological factors that are involved at the Colombian level and at the Boyacá level is carried out. To finalize the diagnosis, a radiation and energy analysis of the involved area is performed.